2021
DOI: 10.1039/d1lc00356a
|View full text |Cite
|
Sign up to set email alerts
|

A compact integrated microfluidic oxygenator with high gas exchange efficiency and compatibility for long-lasting endothelialization

Abstract: A novel microfluidic architecture allowing simple parallel stacking of the different 4 inch circular units of curved blood capillaries covering a maximal surface area with high compacity is proposed for blood oxygenation at high flow rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In a second step, the tumor physiopathology will be reproduced by culturing endothelial cells in the external channel until confluence. To ensure optimal cell attachment, the surface of the device will be suitably treated, for instance by coating it with a mixture of albumin and heparin, as described previously [63]. Then, their barrier function can be modulated by exposing the cells to different cytokines to mimic the increased permeability and retention (EPR) effect observed in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In a second step, the tumor physiopathology will be reproduced by culturing endothelial cells in the external channel until confluence. To ensure optimal cell attachment, the surface of the device will be suitably treated, for instance by coating it with a mixture of albumin and heparin, as described previously [63]. Then, their barrier function can be modulated by exposing the cells to different cytokines to mimic the increased permeability and retention (EPR) effect observed in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The other limitation of our study is that the vessel model was produced under a static condition. While the advantage of the static culture is that it does not cause any mechanotransduction associated with shear stress on the endothelial cells during cell culture, the real in vivo situation always involved shear stress [ 87 ]. Further study will be needed to investigate the effect of different cell culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These microfluidic artificial lungs (µALs) can exhibit µm-tall artificial capillaries, thereby increasing gas exchange efficiency and achieving physiologic blood flow paths, potentially increasing biocompatibility compared to current alternatives. To date, our and other research groups have demonstrated small-scale, single-layer two-dimensional (2D) µALs with record gas exchange efficiency [10,11], biomimetic blood flow networks [10][11][12][13][14][15][16][17][18], surface coatings to reduce protein and platelet deposition and increase lifetime [15,[19][20][21][22], and have also shown that endothelial cells can be grown in microfluidic blood flow networks and significantly reduce thrombus area [16,[23][24][25]. Manufacturing techniques have been demonstrated to increase the blood flow capacity of µAls and move these devices towards clinical application [11,14,16,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%